2014
DOI: 10.1016/j.metabol.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Markers of endothelial cell dysfunction are increased in human omental adipose tissue from women with pre-existing maternal obesity and gestational diabetes

Abstract: This study demonstrated the presence of abnormal expression and secretion of angiogenic proteins and adhesion molecules in omental adipose tissue, but not placenta, from pregnant women with GDM and pre-existing maternal obesity. Increased angiogenic and adhesion molecules released from adipose tissue may affect angiogenesis, inflammation and or lipid and glucose metabolism in both mum and her offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 78 publications
6
50
0
3
Order By: Relevance
“…Indeed, women with GDM have increased circulating sICAM1 and sVCAM1 levels (Mordwinkin et al 2013). My recent studies have also shown that the expression and secretion of markers of endothelial cell dysfunction are increased in adipose tissue from women with GDM (Lappas 2014b). In this study, the NOD1 ligand iE-DAP induced adipose tissue expression and secretion of ICAM1 and VCAM1.…”
Section: Figuresupporting
confidence: 52%
“…Indeed, women with GDM have increased circulating sICAM1 and sVCAM1 levels (Mordwinkin et al 2013). My recent studies have also shown that the expression and secretion of markers of endothelial cell dysfunction are increased in adipose tissue from women with GDM (Lappas 2014b). In this study, the NOD1 ligand iE-DAP induced adipose tissue expression and secretion of ICAM1 and VCAM1.…”
Section: Figuresupporting
confidence: 52%
“…In the context of GDM, the link between the disease and future type 2 DM is well established. In addition, recent studies have found that GDM is an independent risk factor for recurrent GDM (6, 7), long-term cardiovascular morbidity (16,25), and vascular endothelial dysfunction (12)(13)(14). To date, data on the link between GDM and future risk for long-term maternal renal disease is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to metabolic aspects, GDM was also linked to vascular endothelial dysfunction (12)(13)(14). Bo et al (15) followed women with GDM and normal pregnancy years after delivery and compared biochemical markers of vascular endothelial dysfunction in their blood.…”
mentioning
confidence: 99%
“…Validation of these immunohistochemical results was performed by quantitative RT-PCR, as there was significant decrease in CD105 and CD29 genes expression in older ages compared with the younger ones. Although RT-PCR was used frequently to assess the expression of hematopoietic/endothelial cell-related gene CD34 (Fukuchi et al, 2004) and MSCs genes CD105 (Munaut et al, 2008;Sitras et al, 2009;Lappas, 2014) and CD29 (Meinhardt et al, 2014) in human umbilical vein endothelial cells and placenta-derived stem cells, unfortunately, no previous studies have investigated the impact of age on the expression of fetal stem cell makers or genes in general or placental stem cells in specific. These age-related changes observed in the DB, which was derived from the endometrium, may be at least partly explained based on the results of some previous studies that focused on endometrial aging.…”
Section: Discussionmentioning
confidence: 99%